(untitled) (Proceedings of the International Conference on Public Health, 2017)
The evaluation of Tuberculosis (TB) surveillance system conducted at the Health Office of Gresik Regency, Province of East Java showed that there was less data quality, due to incompatibility or incomplete data input from Primary Health Center (Puskesmas). This situation caused officers at the district health service level had to validate. "Simple Web" is a software that was developed to help validation run easily without the huge cost and effort required. The objective of the study was to evaluate the successful of the development of "Simple Web" based on the DeLone and Mc Lean approach model. The study was conducted on 30 of 37 existing Puskesmas. User satisfaction scores of Information System (IS) success factors based on the DeLone and McLean IS Success Model were used to evaluate IS performance after Simple Web was introduced. Data analysis was done by Path Analysis using Lisrel 8.80 for Student. The result showed that the development of Simple Web got positive appreciation from health officers. The software was secure and easy to operate.The relationships among IS success factors were also analyzed to identify the important factors influencing. Information System has no significant relationship with Use and User Satisfaction. And, Service Quality and Quality System has significant relationship with Use and User Satisfaction.